Ultraviolet B Radiation Stimulates the Interaction between Nuclear Factor of Activated T Cells 5 (NFAT5) and Nuclear Factor-Kappa B (NF-κB) in Human Lens Epithelial Cells. (3rd July 2017) - Chung, Inyoung; Hah, Young-Sool; Ju, SunMi; Kim, Ji-Hye; Yoo, Woong-Sun; Cho, Hee-Young; Yoo, Ji-Myong; Seo, Seong-Wook; Choi, Wan-Sung; Kim, Seong-Jae
ABSTRACT: Purpose : Nuclear factor-kappa B (NF-κB) has been proposed as a therapeutic target for the treatment of cataracts. The authors investigated the relationship between nuclear factor of activated T cells 5 (NFAT5) and NF-κB in ultraviolet B (UVB)-irradiated human lens epithelial (HLE) cells. Methods : Human lens epithelial B-3 (HLE-B3) cells were exposed to UVB light at a dose of 10 mJ/cm 2 and then incubated for 24 h. Cell viability was assessed by using the Cell Counting Kit-8 (CCK-8) assay. Gene expression level of NFAT5 was determined using real-time quantitative polymerase chain reaction (qPCR). Protein expression levels of NFAT5, NF-κB p65, and α-smooth muscle actin (α-SMA) and the association of NFAT5 with the NF-κB p65 subunit were measured by Western blot analysis and a co-immunoprecipitation assay, respectively. The cellular distribution of NFAT5 and NF-κB p65 was examined by triple immunofluorescence staining. Results : At 24 h after UVB exposure, cell viability significantly decreased in a dose-dependent manner, and UVB light (15 and 20 mJ/cm 2 ) significantly increased the ROS generation. UVB irradiation increased NFAT5 mRNA and protein levels and increased phosphorylation of NF-κB in HLE-B3 cells. α-SMA protein levels were increased in the irradiated cells. In addition, NFAT5 and NF-κB translocated from the cytoplasm to the nucleus, and binding between the p65 subunit and NFAT5 was increased. Conclusions : Exposure to UVB radiation induces nuclear translocation and stimulates binding between NFAT5 and NF-κB proteins in HLE-B3 cells. These interactions may form part of the biochemical mechanism of cataractogenesis in UVB-irradiated HLECs.